The Dyobelba tectopediosa species-group (Acari: Oribatida: Damaeidae) from the Southeastern USA, with a key to world species of Dyobelba and notes on their distribution - Bayartogtokh, Badamdorj; Norton, Roy A. (Zootaxa, 2007)
Species of the small oribatid mite genus Dyobelba (Damaeidae) mostly inhabit forest litter in the Northern Hemisphere. Herein we redescribe Dyobelba tectopediosa Jacot and propose four related species (D. behanae sp. nov., D. crossleyi sp. nov., D. dindali sp. nov. and D. granulata sp. nov.) that form an apparently monophyletic group characterized by unusual alveolate sculpturing on the prodorsum. Members of this group inhabit various forest types in the southeastern USA, particularly in the southern Appalachian Mountains. Descriptions are based only on adults, except all instars are described for D. dindali, including the full ontogeny of leg setation, using material from a laboratory culture. A diagnostic key to adults of the 11 known species of Dyobelba is given, along with summaries of their geographical and ecological distributions.